Efficacy and safety of cyclosporine A in the treatment of idiopathic membranous nephropathy in an Asian population - Lin S; Li HY; Zhou T; Lin W (Dove Medical Press, 2019)
Shujun Lin,1 Hong-Yan Li,2 Tianbiao Zhou,1 Wenshan Lin11Department of Nephrology, The Second Affiliated Hospital of Shantou University Medical College, Shantou 515041, People’s Republic of China; 2Department of Nephrology, Huadu District People’s Hospital of Guangzhou, Southern Medical University, Guangzhou 510800, People’s Republic of ChinaIntroduction: The efficacy of cyclosporine A (CsA) in the treatment of idiopathic membranous nephropathy (IMN) is unclear. This meta-analysis was conducted to assess the efficacy and the safety of CsA in the treatment of IMN in Asians.Methods: We searched the Pubmed, China Biomedical Database, CNKI, Wanfang Data, VIP, and EMBASE (November 30, 2018) systematically to identify the appropriate randomized controlled trials (RCTs) reporting the efficacy and the safety of CsA and glucocorticoid (GC) treatment vs other immunosuppressants and GC on patients with IMN in Asian populations.Results: The CsA treated group entered complete remission (CR) faster (3 months) than a cyclophosphamide (CTX) group. While the CsA group lower inefficacy rates and higher total remission (TR, CR, or partial remission) than the CTX group in the total treatment (3 months, 6 months, and 12 months), it had a higher relapse rate. As for the CsA group vs the tacrolimus (TAC) group, the TAC had a significant effect in increasing the CR and the TR, with decreased no remission. With the therapeutic regimens of CsA+GC vs CTX+GC, the CsA exhibited better efficacy in lowering the proteinuria levels only at 12 months, not at 3 months or 6 months. Severe events like leucopenia, hemorrhagic cystitis, and alopecia were observed in the CTX group. Gingival hyperplasia, hirsutism, and elevated blood pressure were reported only in the CsA group. Gastrointestinal syndrome, liver function lesion, happened more frequently in the CTX group, and elevated uric acid was more common in the CsA group.Conclusions: In brief, the CsA has better efficacy than the CTX group in the Asian population, with mild adverse effects but higher relapse rates in short-term treatment.Keywords: idiopathic membranous nephropathy, cyclosporine A, cyclophosphamide, mycophenolate mofetil, tacrolimus